PENGARUH INTENSITAS PAPARAN KONTEN DAN KUALITAS INFORMASI TERHADAP TINGKAT KEPERCAYAAN PADA INFORMASI KESEHATAN MENTAL DI KALANGAN GENERASI Z PENGGUNA TIKTOK - Niken Yuly Prasetya; wiwid Noor Rakhmad (Interaksi Online, 2026)
This research is driven by the phenomenon of increasing content consumption on TikTok, particularly the prevalence of low-quality mental health content that is easily trusted by Generation Z. The high level of TikTok usage among this generation creates an ecosystem of massive information exposure with minimal curation, raising serious concerns regarding the quality of mental health knowledge shaped through the platform. This study aims to determine the influence of content exposure intensity and information quality on the level of trust in mental health content among Generation Z TikTok users. This research employs a quantitative explanatory approach using a survey method. The theoretical frameworks utilized are Cultivation Theory and Information Integration Theory to explain the mechanism of trust formation in the context of digital content consumption. Data from 100 respondents were analyzed using simple linear regression analysis. The results indicate that the intensity of content exposure has a weak influence on the level of trust in mental health information, while information quality has a moderate influence on the level of trust. These findings contribute new insights to Cultivation Theory and Information Integration Theory and suggest that TikTok users, especially Generation Z, should develop a critical attitude when consuming mental health content, such as re-verifying information with credible sources